The detection of multivessel coronary artery disease: the value of quantitative myocardial blood flow and coronary flow reserve assessment. (25th November 2020) - Zavadovskiy, K; Mochula, A; Maltseva, A; Boshchenko, A; Baev, A; Andreev, S; Liga, R; Gimelli, A
Abstract: Background/Introduction: The recent Cadmium-Zinc-Telluride (CZT) camera for MPS allows evaluating absolute MBF and CFR, possibly increasing the accuracy in detecting of multivessel CAD. Purpose: To evaluate the accuracy of myocardial blood flow (MBF) and coronary flow reserve (CFR) quantitation performed by myocardial perfusion scintigraphy (MPS) for the detection of multivessel coronary artery disease (CAD). Methods: Fifty-two patients with suspected or known CAD were enrolled in the study. All patients underwent CZT MPS, with the evaluation of MBF and CFR, followed by invasive coronary angiography. According to MPS and coronary angiography results, patients were divided into three groups. 1) non-obstructive CAD and normal MPS scan (control group) (n=7), 2) one vessel disease (1VD) (n=16), with significant coronary stenosis (≥70%) in one major epicardial coronary artery, 3) multivessel disease (MVD) group (n=29), with two or more major epicardial coronary arteries with (≥70%) stenoses or with ≥50% LMA stenosis. Results: Absolute MBF and CFR were significantly reduced in patients with MVD as compared to those with 1VD [0.93 (IQR 0.76; 1.39) vs 1.94 (1.37; 2.21) ml/min/g, p=0.00012] and [1.4 (IQR 1.02; 1.85) vs 2.3 (1.8; 2.67), p=0.0004], respectively. The Syntax score correlated with global stress MBF (ρ=−0.64; p<0.0001) and CFR (ρ=−0.53; p=0.0003). ROC analysis showed higher sensitivity and specificity for stress MBF (85.2% and 81%), and CFR (88.9% and 80%) compared with semiquantitative MPS stress evaluation (69% and 69%). Multivariate regression analysis showed that only stress MBF [OR (95% CI) 0.59 (0.42–0.82); p<0.0003] was an independent predictor of MVD. Conclusion: The use of absolute myocardial blood flow analysis with the CZT camera may identify high risk patients, such as those with multivessel disease. This approach could be used in clinical practice, increasing the accuracy in the evaluation of patients with known or suspected coronary artery disease. Funding Acknowledgement: Type of funding source: None